Intelligent thermal control metamaterial with ultra-low solar absorption ratio and preparation method thereof
Patent Information
- Application Number
- CN202611360957.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明要解决现有基于VO2基智能热控涂层难以同时解决太阳吸收比高、宽波段发射率动态调控能力不足、相变温度偏高及微纳结构制备工艺复杂的问题,进而提供一种超低太阳吸收比的智能热控超材料及其制备方法
[0019]本发明能够在降低太阳吸收比的同时,实现更宽的红外发射率调制幅度,且相变温度在室温附近。通过调节光子晶体的中心波长,可在太阳光谱范围内形成高反射带,从而降低热控涂层的吸收比。与底部的金属高反射层,介质层和相变层耦合,利用VO2薄膜低温红外高透过,高温红外高反射的相变特性,可以实现低温低发射率,高温高发射率。通过不同含量元素掺杂可改变VO2相变温度,实现多场景多地区应用。且本发明的材料选择具有多样性且制备方法简单、成本低、可重复性高和可大面积制备等特点。
Smart Images

Figure CN122879653A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of space thermal control materials technology. Background Technology
[0002] During their operation in orbit, spacecraft are exposed to complex space environments, including solar radiation, high vacuum, cryogenic background, and periodic temperature fluctuations. The photothermal properties of thermal control materials on the spacecraft surface, especially solar absorptivity and infrared emissivity, directly affect the spacecraft's temperature stability and operational reliability. Traditional space thermal control coatings typically rely on low solar absorptivity and high infrared emissivity to achieve passive thermal equilibrium, but their thermal radiation properties are relatively fixed and difficult to adapt to the complex and variable space thermal environment.
[0003] Intelligent thermal control technology mainly includes active and passive thermal control technologies. Active thermal control technology typically relies on external power sources, sensors, or control systems, resulting in complex system structures, high additional energy consumption, and limited long-term reliability, thus restricting its application in energy- and mass-constrained scenarios such as space payloads and microsatellites. In contrast, passive intelligent thermal control technology relies on the material's own response to temperature changes to achieve adaptive adjustment of thermal radiation performance, requiring no external energy input and offering advantages such as simple structure, high energy efficiency, and strong adaptability. Vanadium dioxide (VO2) thermochromic materials are typical passive intelligent thermal control materials, capable of undergoing a reversible metal-insulator phase transition near the phase transition temperature, accompanied by changes in infrared optical properties, thereby achieving temperature-responsive thermal radiation regulation. However, existing VO2-based intelligent thermal control coatings generally suffer from high solar absorptivity, easily introducing additional heat input under solar irradiation conditions, leading to increased coating surface temperature and weakening its adaptive heat dissipation capability and overall thermal control efficiency. Therefore, how to reduce the solar absorptivity while maintaining the infrared regulation capability of VO2 is a crucial technical problem that urgently needs to be solved for VO2-based intelligent thermal control coatings.
[0004] To reduce solar absorption and improve emissivity modulation performance of VO2-based smart thermal control coatings, optimization strategies such as surface arrays and photonic crystal structures have been proposed. For example, the paper *Advanced Photonics*, Vol. 6, Issue 4, 046006 (Smart and Flexible Optical Solar Reflectors for Passive Radiative Cooling Regulation in Space Using a W:VO2 Metasurface) reported a VO2 / HfO2 / Ag structure with an infrared emissivity modulation amplitude of 0.72 in the 8μm~13μm band and a solar absorptivity of approximately 0.28, but with a phase transition temperature as high as 68℃; *Science* 374, 1504-1509 (2021) (Temperature-adaptive radiative coating for all-season household thermal...) A novel VO2 / BaF2 / Ag structure was proposed, which can achieve an infrared emissivity modulation amplitude of approximately 0.70 in the 8μm~13μm band, a solar absorptivity of approximately 0.25, and a phase transition temperature of approximately 22℃. However, its spectral design is only compatible with the 8μm~13μm atmospheric window and cannot meet the on-orbit full-spectrum thermal radiation regulation requirements of spacecraft in the 2.5μm~25μm range. Nanophotonics, 2026; 15:e7001 (Smart and Flexible Optical SolarReflectors for Passive Radiative Cooling Regulation in Space Using a W:VO2Metasurface) proposed a structure using (YF3 / ZnS) to achieve this. 12 The / VO2 / SiO2 / Al structure can reduce the solar absorptivity to 0.22 and the phase transition temperature to about 30°C, but its infrared emissivity modulation amplitude drops to 0.33.
[0005] The above studies demonstrate the feasibility of optimizing the spectral performance of VO2-based smart thermal control coatings through surface arrays or photonic crystal structures. However, existing solutions still have the following shortcomings: First, the solar absorptivity remains high, easily introducing additional heat input under solar irradiation conditions; second, the spectral design is difficult to adapt to the 2.5μm~25μm wide-band thermal radiation control requirements in space thermal control environments, resulting in limited emissivity control capabilities; third, the phase transition temperature is high, making it difficult to match the need for adaptive control within a suitable temperature range in actual space thermal control scenarios; fourth, surface arrays typically involve complex patterning or precise structural control, making the fabrication process cumbersome and difficult to meet the requirements for large-area, low-cost, and scalable fabrication. Therefore, it is necessary to develop a VO2-based smart thermal control coating that combines low solar absorptivity, suitable phase transition temperature, wide-band infrared emissivity control capabilities, and easy scalable fabrication. Summary of the Invention
[0006] This invention aims to address the problems of existing VO2-based smart thermal control coatings, which cannot simultaneously solve the issues of high solar absorptivity, insufficient dynamic control capability of wide-band emissivity, high phase transition temperature, and complex micro / nano structure fabrication processes. It provides a smart thermal control metamaterial with ultra-low solar absorptivity and its fabrication method.
[0007] A smart thermal control metamaterial with ultra-low solar absorptivity consists of a semiconductor substrate, an infrared high-reflectivity metal layer, a dielectric layer, a phase transition layer, and a photonic crystal layer, from bottom to top.
[0008] The photonic crystal layer is composed of alternating layers of low refractive index and high refractive index; and the total number of low refractive index and high refractive index layers in the photonic crystal layer is 4 to 16.
[0009] A method for preparing an intelligent thermal control metamaterial with ultra-low solar absorptivity, comprising the following steps:
[0010] I. Preparation of Infrared High-Reflectivity Metal Layer:
[0011] An infrared-highly reflective metal layer is deposited on the surface of a semiconductor substrate using electron beam evaporation technology with a highly reflective metal as the evaporation source.
[0012] II. Preparation of the dielectric layer:
[0013] Electron beam evaporation technology is used to deposit a dielectric layer on the surface of an infrared highly reflective metal layer using an infrared transparent material as the evaporation source.
[0014] III. Preparation of Phase Change Layers:
[0015] A VO2-doped thin film was deposited on the surface of a dielectric layer using high-energy pulsed magnetron sputtering technology, and then annealed to obtain a phase change layer.
[0016] IV. Fabrication of Photonic Crystal Layers:
[0017] A method for preparing intelligent thermally controlled metamaterials with ultra-low solar absorptivity is achieved by using electron beam evaporation deposition technology, with low-refractive-index and high-refractive-index materials as evaporation sources, and sequentially depositing photonic crystal layers on the surface of a phase transition layer.
[0018] The beneficial effects of this invention are:
[0019] This invention achieves a wider infrared emissivity modulation range while reducing solar absorptivity, with the phase transition temperature near room temperature. By adjusting the center wavelength of the photonic crystal, a high-reflectivity band can be formed within the solar spectrum, thereby reducing the absorptivity of the thermal control coating. Coupled with the bottom high-reflectivity metal layer, dielectric layer, and phase transition layer, the phase transition characteristics of VO2 thin films—high infrared transmittance at low temperatures and high infrared reflectance at high temperatures—can achieve low emissivity at low temperatures and high emissivity at high temperatures. The VO2 phase transition temperature can be altered by doping with different amounts of elements, enabling applications in multiple scenarios and regions. Furthermore, this invention offers diverse material choices and features simple, low-cost, highly reproducible, and large-area fabrication capabilities. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the structure of the intelligent thermal control metamaterial with ultra-low solar absorptivity of the present invention. 1 is a high refractive index layer, 2 is a low refractive index layer, 3 is a phase change layer, 4 is a dielectric layer, 5 is an infrared high reflectivity metal layer, and 6 is a semiconductor substrate.
[0021] Figure 2 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 1 are shown.
[0022] Figure 3 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 2 are shown.
[0023] Figure 4 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 3 are shown.
[0024] Figure 5 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 4 are shown.
[0025] Figure 6 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 5 are shown.
[0026] Figure 7The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 6 are shown.
[0027] Figure 8 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 7 are shown.
[0028] Figure 9 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 8 are shown. Detailed Implementation
[0029] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any combination of the specific embodiments.
[0030] Specific implementation method one, combined with Figure 1 Detailed description: This embodiment is a smart thermal control metamaterial with ultra-low solar absorptivity, which is composed of a semiconductor substrate, an infrared high reflectivity metal layer, a dielectric layer, a phase transition layer and a photonic crystal layer from bottom to top;
[0031] The photonic crystal layer is composed of alternating layers of low refractive index and high refractive index; and the total number of low refractive index and high refractive index layers in the photonic crystal layer is 4 to 16.
[0032] The beneficial effects of this embodiment are:
[0033] This embodiment achieves a wider infrared emissivity modulation range while reducing the solar absorptivity, with the phase transition temperature near room temperature. By adjusting the center wavelength of the photonic crystal, a high-reflectivity band can be formed within the solar spectrum, thereby reducing the absorptivity of the thermal control coating. Coupled with the bottom high-reflectivity metal layer, dielectric layer, and phase transition layer, the phase transition characteristics of the VO2 thin film—high infrared transmittance at low temperatures and high infrared reflectance at high temperatures—can achieve low emissivity at low temperatures and high emissivity at high temperatures. The VO2 phase transition temperature can be altered by doping with different amounts of elements, enabling applications in multiple scenarios and regions. Furthermore, this embodiment offers diverse material choices and features simple, low-cost, highly reproducible, and large-area fabrication capabilities.
[0034] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the infrared high reflectivity metal layer is made of Al, Au, Ag, or ITO; and the thickness of the infrared high reflectivity metal layer is 100nm~200nm. Everything else is the same as in Specific Implementation Method One.
[0035] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the dielectric layer is BaF2, MgF2, CaF2, HfO2, SiO2, or Al2O3; and the thickness of the dielectric layer is 900nm~1200nm. Everything else is the same as in Specific Implementation Method One or Two.
[0036] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the phase transition layer is a W-doped VO2 layer; and the thickness of the phase transition layer is 10nm~70nm. Everything else is the same as Specific Implementation Methods One to Three.
[0037] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the low refractive index layer is CaF2, BaF2, or MgF2; and the thickness of the low refractive index layer is 70nm~240nm. Everything else is the same as Specific Implementation Methods One to Four.
[0038] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the high refractive index layer is ZnS, ZnSe, or Si; and the thickness of the high refractive index layer is 20nm~110nm. Everything else is the same as Specific Implementation Methods One to Five.
[0039] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the semiconductor substrate is Si, SiO2, GaN, or Al2O3. Everything else is the same as in Specific Implementation Methods One to Six.
[0040] Specific Implementation Method Eight: This implementation method describes a method for preparing an intelligent thermal control metamaterial with an ultra-low solar absorptivity, which is carried out according to the following steps:
[0041] I. Preparation of Infrared High-Reflectivity Metal Layer:
[0042] An infrared-highly reflective metal layer is deposited on the surface of a semiconductor substrate using electron beam evaporation technology with a highly reflective metal as the evaporation source.
[0043] II. Preparation of the dielectric layer:
[0044] Electron beam evaporation technology is used to deposit a dielectric layer on the surface of an infrared highly reflective metal layer using an infrared transparent material as the evaporation source.
[0045] III. Preparation of Phase Change Layers:
[0046] A VO2-doped thin film was deposited on the surface of a dielectric layer using high-energy pulsed magnetron sputtering technology, and then annealed to obtain a phase change layer.
[0047] IV. Fabrication of Photonic Crystal Layers:
[0048] A method for preparing intelligent thermally controlled metamaterials with ultra-low solar absorptivity is achieved by using electron beam evaporation deposition technology, with low-refractive-index and high-refractive-index materials as evaporation sources, and sequentially depositing photonic crystal layers on the surface of a phase transition layer.
[0049] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Method Eight in that the annealing described in step three is specifically carried out under an argon atmosphere, with a heating rate of 1℃ / min~4℃ / min to 300℃~400℃, and held at 300℃~400℃ for 1h~5h. Other aspects are the same as or identical to Specific Implementation Method Eight.
[0050] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Method Eight or Nine in that the photonic crystal layer described in step four is composed of alternating stacks of CaF2 and Si layers, specifically prepared according to the following steps: using electron beam evaporation deposition technology, with CaF2 or Si as the evaporation source, under a vacuum degree of 10... -3 Pa~10 -5 Under the conditions of Pa, substrate temperature of 25℃~300℃, CaF2 layer evaporation rate of 0.1nm / s~0.5nm / s or Si layer evaporation rate of 0.1nm / s~0.5nm / s, CaF2 layer and Si layer are sequentially and alternately deposited on the surface of the phase change layer. Other aspects are the same as in specific embodiments eight or nine.
[0051] The beneficial effects of the present invention are verified using the following embodiments:
[0052] Example 1:
[0053] A smart thermal control metamaterial with ultra-low solar absorptivity consists of a semiconductor substrate, an infrared high-reflectivity metal layer, a dielectric layer, a phase transition layer, and a photonic crystal layer, from bottom to top.
[0054] The photonic crystal layer is composed of alternating layers of low refractive index and high refractive index; and the total number of low refractive index and high refractive index layers in the photonic crystal layer is 4; the photonic crystal layer consists of a low refractive index layer, a high refractive index layer, a low refractive index layer and a high refractive index layer from bottom to top, with thicknesses of 230nm, 100nm, 160nm and 70nm respectively.
[0055] The infrared high reflectivity metal layer is Al; the thickness of the infrared high reflectivity metal layer is 150 nm.
[0056] The dielectric layer is BaF2; the thickness of the dielectric layer is 1000 nm.
[0057] The phase transition layer is a W-doped VO2 layer, and W accounts for 2% of the total number of W and V atoms; the thickness of the phase transition layer is 40 nm.
[0058] The low-refractive-index layer is CaF2;
[0059] The high refractive index layer is Si;
[0060] The semiconductor substrate is a quartz substrate.
[0061] The above-mentioned method for preparing an intelligent thermal control metamaterial with ultra-low solar absorptivity is carried out according to the following steps:
[0062] I. Preparation of Infrared High-Reflectivity Metal Layer:
[0063] Electron beam evaporation technology was used, with Al as the evaporation source, at a vacuum degree of 10. -4 An infrared high reflectivity metal layer is deposited on the surface of a semiconductor substrate under the conditions of Pa, substrate temperature of 50℃ and evaporation rate of 0.1nm / s~0.5nm / s.
[0064] The semiconductor substrate was obtained after pretreatment, which involved ultrasonic cleaning with acetone, anhydrous ethanol and deionized water in sequence, followed by drying with a high-pressure nitrogen gun.
[0065] II. Preparation of the dielectric layer:
[0066] Electron beam evaporation technology was used, with BaF2 as the evaporation source, at a vacuum degree of 10. -4 Under the conditions of Pa, substrate temperature of 100℃, and evaporation rate of 0.1nm / s~0.5nm / s, a dielectric layer is deposited on the surface of an infrared high reflectivity metal layer.
[0067] III. Preparation of Phase Change Layers:
[0068] High-energy pulsed magnetron sputtering technology was employed, using 2% W-doped metallic V as the target material, at a vacuum level of 10... -4 Under the conditions of Pa, frequency of 400Hz, pulse width of 50μm, power of 180W, voltage of 600V, deposition pressure of 0.9Pa, argon flow rate of 80sccm, oxygen flow rate of 1.5sccm, and substrate temperature of 200℃, a VO2-doped thin film was deposited on the surface of the dielectric layer. Finally, under an argon atmosphere, the temperature was increased to 400℃ at a heating rate of 1℃ / min and held at 400℃ for 4h to obtain the phase change layer.
[0069] IV. Fabrication of Photonic Crystal Layers:
[0070] Electron beam evaporation deposition technology was employed, using CaF2 as the evaporation source, at a vacuum level of 10. -4Under conditions of Pa, a substrate temperature of 100℃, and a CaF2 layer evaporation rate of 0.1 nm / s to 0.5 nm / s, a CaF2 layer was deposited on the surface of the phase change layer. Then, using Si as the evaporation source, the evaporation was carried out under a vacuum of 10 -4 Under the conditions of Pa, substrate temperature of 100℃ and Si layer evaporation rate of 0.1nm / s~0.5nm / s, Si layers are deposited, and CaF2 layers and Si layers are deposited alternately to form a photonic crystal layer, thus obtaining an intelligent thermal control metamaterial with ultra-low solar absorptivity.
[0071] Example 2: This example differs from Example 1 in that: the thickness of the dielectric layer is 1000 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 5; the photonic crystal layer, from bottom to top, consists of a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, and a low-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, and 160 nm, respectively. Everything else is the same as in Example 1.
[0072] Example 3: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 6; the photonic crystal layers, from bottom to top, are a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, and a high-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, and 70 nm, respectively. Everything else is the same as in Example 1.
[0073] Example 4: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 7; the photonic crystal layers, from bottom to top, are a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, and a low-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, 70 nm, and 110 nm, respectively. Everything else is the same as in Example 1.
[0074] Example 5: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 8; the photonic crystal layers, from bottom to top, are low-refractive-index layer, high-refractive-index layer, low-refractive-index layer, high-refractive-index layer, low-refractive-index layer, high-refractive-index layer, low-refractive-index layer, and high-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, 70 nm, 110 nm, and 40 nm, respectively; the substrate temperature in step two is 150 °C; the substrate temperature in step four is 150 °C. Everything else is the same as in Example 1.
[0075] Example 6: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 9; the photonic crystal layers, from bottom to top, are a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, and a low-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, 70 nm, 110 nm, 40 nm, and 90 nm, respectively; the substrate temperature in step two is 200 °C; the substrate temperature in step four is 200 °C. Everything else is the same as in Example 1.
[0076] Example 7: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 10; the photonic crystal layers, from bottom to top, are a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, and a high-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, 70 nm, 110 nm, 40 nm, 90 nm, and 35 nm, respectively; the substrate temperature in step two is 250 °C; the substrate temperature in step four is 250 °C. Everything else is the same as in Example 1.
[0077] Example 8: This example differs from Example 1 in that: the thickness of the dielectric layer is 1100 nm; the total number of low-refractive-index and high-refractive-index layers in the photonic crystal layer is 10; the photonic crystal layer, from bottom to top, consists of a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, a high-refractive-index layer, a low-refractive-index layer, and a high-refractive-index layer, with thicknesses of 230 nm, 100 nm, 160 nm, 70 nm, 160 nm, 70 nm, 110 nm, 40 nm, 90 nm, and 35 nm, respectively; the substrate temperature in step two is 250 °C; the substrate temperature in step four is 200 °C. Everything else is the same as in Example 1.
[0078] Infrared performance tests were conducted on the intelligent thermal control metamaterials with ultra-low solar absorptivity in Examples 1 to 8: using a Fourier transform infrared spectrometer and a temperature control platform, the infrared reflection spectrum of the devices was tested in the temperature range of 0℃ to 70℃, and then converted into emission spectra.
[0079] Phase transition temperature tests were conducted on the intelligent thermal control metamaterials with ultra-low solar absorptivity in Examples 1 to 8: the changes in infrared reflectivity with temperature during the heating and cooling processes were recorded, and the reflectivity of a single wavelength under different temperature conditions was extracted. These were plotted to obtain the thermal hysteresis loop of the device, and the phase transition temperature T of the device was obtained by performing a first-order derivative on the curve. MIT .
[0080] The reflectivity of the intelligent thermally controlled metamaterials with ultra-low solar absorptivity in Examples 1 to 8 was tested: the device temperature was adjusted (from -60°C to 80°C) using a temperature control device, and its variable-temperature solar band reflectance spectrum was measured to calculate the solar absorptivity α. s .
[0081] Figure 2 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 1 are shown. Figure 3 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 2 are shown. Figure 4 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 3 are shown. Figure 5 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 4 are shown. Figure 6 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 5 are shown. Figure 7 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 6 are shown. Figure 8 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 7 are shown. Figure 9 The low-temperature (M) and high-temperature (R) reflectance spectra of the intelligent thermal control metamaterial with ultra-low solar absorptivity in Example 8 are shown in Table 1; detailed data are shown in Table 1.
[0082] Table 1
[0083]
Claims
1. A smart thermal control metamaterial with ultra-low solar absorptivity, characterized in that... It consists of a semiconductor substrate, an infrared high-reflectivity metal layer, a dielectric layer, a phase transition layer, and a photonic crystal layer from bottom to top. The photonic crystal layer is composed of alternating layers of low refractive index and high refractive index; and the total number of low refractive index and high refractive index layers in the photonic crystal layer is 4 to 16.
2. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The infrared high reflectivity metal layer is made of Al, Au, Ag or ITO; the thickness of the infrared high reflectivity metal layer is 100nm~200nm.
3. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The dielectric layer is BaF2, MgF2, CaF2, HfO2, SiO2 or Al2O3; the thickness of the dielectric layer is 900nm~1200nm.
4. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The phase transition layer is a W-doped VO2 layer; the thickness of the phase transition layer is 10nm~70nm.
5. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The low refractive index layer is CaF2, BaF2 or MgF2; the thickness of the low refractive index layer is 70nm~240nm.
6. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The high refractive index layer is ZnS, ZnSe, or Si; the thickness of the high refractive index layer is 20 nm to 110 nm.
7. The intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 1, characterized in that... The semiconductor substrate is Si, SiO2, GaN or Al2O3.
8. The method for preparing an intelligent thermal control metamaterial with ultra-low solar absorptivity as described in claim 1, characterized in that... It is done in the following steps: I. Preparation of Infrared High-Reflectivity Metal Layer: An infrared-highly reflective metal layer is deposited on the surface of a semiconductor substrate using electron beam evaporation technology with a highly reflective metal as the evaporation source. II. Preparation of the dielectric layer: Electron beam evaporation technology is used to deposit a dielectric layer on the surface of an infrared highly reflective metal layer using an infrared transparent material as the evaporation source. III. Preparation of Phase Change Layers: A VO2-doped thin film was deposited on the surface of a dielectric layer using high-energy pulsed magnetron sputtering technology, and then annealed to obtain a phase change layer. IV. Fabrication of Photonic Crystal Layers: A method for preparing intelligent thermally controlled metamaterials with ultra-low solar absorptivity is achieved by using electron beam evaporation deposition technology, with low-refractive-index and high-refractive-index materials as evaporation sources, and sequentially depositing photonic crystal layers on the surface of a phase transition layer.
9. The method for preparing an intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 8, characterized in that... The annealing described in step three is specifically carried out under an argon atmosphere, with the temperature increased to 300℃~400℃ at a rate of 1℃ / min~4℃ / min, and then held at 300℃~400℃ for 1h~5h.
10. The method for preparing an intelligent thermal control metamaterial with ultra-low solar absorptivity according to claim 8, characterized in that... The photonic crystal layer described in step four is composed of alternating stacks of CaF2 and Si layers, specifically prepared according to the following steps: using electron beam evaporation deposition technology, with CaF2 or Si as the evaporation source, at a vacuum degree of 10... -3 Pa~10 -5 Under the conditions of Pa, substrate temperature of 25℃~300℃, CaF2 layer evaporation rate of 0.1nm / s~0.5nm / s or Si layer evaporation rate of 0.1nm / s~0.5nm / s, CaF2 layer and Si layer are sequentially and alternately deposited on the surface of phase change layer.